National Education Policy 2020: A Roadmap for Holistic Physical Development - Shailja Aswal Bhriguvanshi (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The National Education Policy (NEP) 2020 is a comprehensive document to transform the education system in India. This research paper analyses the importance of physical education and sports under NEP 2020. It discusses how the physical, mental and social development of students is promoted through the integration of physical development and sports in education.
Keywords: National Education Policy 2020; Physical Education; Sports; Overall Development; Educational Policy